KARAKTERISTIK KLINIS MALARIA TROPIKA PADA PASIEN RAWAT INAP DI RUMAH SAKIT UMUM DAERAH MGR. GABRIEL MANEK, SVD ATAMBUA PERIODE SEPTEMBER 2013 - FEBRUARI 2014 - Robertus Brian Junarli; I Ketut Agus Somia (E-Jurnal Medika Udayana, 2017)
Falciparum malaria is the most dangerous type of malaria caused by infection of Plasmodium falciparum. It has atypical prodromal symptoms and hard to differentiate from other types of malaria. It needs fast and prompt treatment since it can cause serious complication including death. This research aim to know characteristics of inpatient with falciparum malaria in Mgr. Gabriel Manek, SVD Atambua public hospital period September 2013 to February 2014. This study was descriptive, which the data was retrospective and taken through cross-sectional on Juny 2014. Through this study, medical records of 71 patients who positively diagnosed as falciparum malaria using thick and thin blood smear as the gold standard of diagnosis were used. The most common patient’s characteristic were female (50.7%), age group 1 to 10 years old (52.1%), with fever and malaise as the chief complaint (100%). Based on axilla temperature, most of the patient had febris (64.8%). Based on hemoglobin level, most of the patient had normal level of hemoglobin (64.8%). Bleeding (15,4%) was the most common complication with petechiae (54.5%) as the most common type of bleeding. Among antimalarial drugs, intravenously given quinine (46.5%) was the drug used the most. Most of the patients were hospitalized for 4 days (22.5%). Based on the result of treatment, most of the patient leaving hospital in state of recovery (67.6%). The results of this study can be used as evaluation for medical personnel especially in Mgr. Gabriel Manek, SVD Atambua public hospital in order to give better treatment for patient with falciparum malaria. Keywords: falciparum malaria, characteristic, prevalence